Advanced Imaging in the Diagnosis of Gout and Other Crystal Arthropathies - Teh, James; McQueen, Fiona; Eshed, Iris; Plagou, Athena; Klauser, Andrea (Seminars in Musculoskeletal Radiology, 2018)
In recent years significant advances have been made in imaging techniques. Dual-energy computed tomography has revolutionized the ability to detect and quantify gout. The key ultrasound features of gout have been defined. Magnetic resonance imaging is an excellent modality for demonstrating the extent and severity of crystal arthropathies, but the findings may be nonspecific. This article summarizes the use of advanced imaging techniques in the diagnosis and assessment of gout and other crystal arthropathies.
Keywords: crystal arthropathy; gout; dual-energy computed tomography; magnetic resonance imaging; ultrasound